Enhancing rosemary growth and essential oil quality through multi-strain PGPR and organic fertilization - Oztan, Melike; Cakmakci, Ramazan; Angin, Hilal; Coban, Furkan (Taylor & Francis Ltd, 2026)
Rosemary (Rosmarinus officinalis L.) is a valuable aromatic herb widely used for its essential oils with culinary and medicinal applications. With increasing interest in sustainable agriculture, the use of beneficial microorganisms is gaining importance as an alternative to synthetic inputs. This field study investigated the effects of mineral fertilizer (100 kg ha-1 nitrogen, 100 kg ha-1 phosphorus, and 50 kg ha-1 potassium), farmyard manure (20 tons ha-1 cattle manure), and multi-strain bacterial inoculants on the growth, yield, and essential oil characteristics of rosemary. Bacterial treatments included five single strains (Pseudomonas fluorescens RC512 and RC536, Bacillus megaterium RC16, B. subtilis RC210, and B. licheniformis RC502) and two three-strain combinations (RC512 + RC210 + RC16 and RC536 + RC210 + RC502). The fertilizers were applied during soil preparation, while biofertilizer treatments involved dipping seedling roots in bacterial suspensions before planting. Most microbial treatments significantly enhanced plant height, number of branches, herb biomass, leaf yield, and essential oil content and yield, with some combinations performing comparably or even better than mineral fertilizer. The essential oils were dominated by oxygenated monoterpenes and monoterpene hydrocarbons, including 1,8-cineole, alpha-pinene, camphor, verbenone, borneol, and linalool. These findings suggest that selected bacterial inoculants could improve rosemary productivity and oil quality, offering an eco-friendly alternative to conventional fertilization practices.
Keywords: Rosmarinus Officinalis; Biofertilizer; Volatile Compounds; Pgpr Inoculation; Sustainable Agriculture